IMPLEMENTATIONS OF MULTICULTURAL EDUCATION AS A SCHOOL CULTURE AT KRIDA NUSANTARA INTEGRATED SENIOR HIGH SCHOOL - Sunani, Sunani (Universitas Pendidikan Indonesia, 2017)
The primary purpose of this study is to describe the implementation of multicultural education at Krida Nusantara integrated high school. The study focuses on four main points; the school policy, the implementation and the dominant factors that influence the policy, and the implementation results. A descriptive qualitative approach is taken in the study and the data is collected through interviews and case studies. The study concludes that the school's multicultural education policy is applied based on the school founding fathers’ philosophy, which emphasizes on merging nationalist and religious values. Those values are then implemented in form of academic and non-academic programs. Apart from that, students' plurality values that are embedded in their school life serve as the most influential factor in implementing the multicultural education policy.